DEVELOPMENT OF PREDICTIVE MAINTENANCE DATA ANALYTIC FOR INTERNET OF THINGS (IOT) IMPLEMENTATION - Koh, Xu-Ming (2017)
For the past few decades, most of the manufacturing plants and factories has been using periodic and preventive maintenance to maintain their equipments and instrument in the optimum state. However, these maintenance techniques sometimes will lead to unnecessary maintenance thus ends up with labour extensive and high cost problems. Predictive maintenance in the other hand allows the users to predictive future possible errors for a particular equipment or instrument. This allows us to reduce the frequency of needed maintenance unlike periodic and preventive maintenance.